Why Most Africa is Poor: The Case of One Village in Limpopo Province: Towards Empowerment - Pitso , Teboho (Journal of Economic Development, Environment and People, 2025)
<!--StartFragment--> The study offers preliminary findings on the research project that was undertaken at One village in Limpopo Province. It was investigating the impact of the mining activity at one village whose residents languish in abject poverty notwithstanding that the mining sector in Limpopo Province are 108 and generates an annual revenue of R237,7 billion. Most villagers are victims of colonialism that created illusions such as that of education and Christian church to stunt and de-inferioritise villagers into believing the absurdity that the reason they are poor is because they lack knowledge and faith that God will intervene while the mining sector keeps eating away and contaminating their socio-ecological spaces. The results show that villagers are generationally stunted and de-inferioritised leading to years of inactivity. Agricultural and animal husbandry activities are history. Naturally growing fruits such as bananas, mango, avocados have been lost to a community that relies on social grants to survive. This has led to my new research which is community-driven I call Vukuzakhe research method. This method consists of various workshops of which the first two are dedicated to de-stunting and de-inferioritising the villagers. <!--EndFragment-->